Design and Implementation of Network Forensic System Based on Intrusion Detection Analysis - Jiang Liu; Tian Guiyan; Zhu Shidong (2012 International Conference on Control Engineering and Communication Technology, 2012)
To meet the needs of the digital evidence on legal action proceedings, network forensics technology plays an important role in the process of fighting against computer crime and hacking crime. To try to solve some problems of eliminating intrusion track after hacking and some drawbacks of network forensics products, in this paper, we present a network forensic solution which adopts dynamic and static methods to analyze network intrusion data and make detailed records of the data and log. This network forensics solution is able to carry out deep and multi-angle forensic analysis with network evidence, and can ensure the reliability and credibility of the network evidence through effective technical methods.